Assessment of Task Implementation and Coordination of Joint Business Group (KUBE) Program - Silaban, Himsar (UI Scholars Hub, 2014)
Joint Business Group (KUBE) is one of Social Welfare Programs (PROKESOS) created by the Ministry of Social Affairs to build the skills of solving problem, fulfilling daily needs and developing self-potentials of the poor. The success of KUBE depends on various aspects, one of which is the service provider, i.e. government officials who implement KUBE program in the field. The research was conducted in areas that have implemented KUBE. The research locations were determined based on purposive technique in Galih Pakuan village, Bulu Limbangan Sub-district, Garut District, West Java, and Purworejo village, Negeri Katon Sub-district, Pesawaran District, Lampung. The data were collected through interviews, using guidelines of interview, observation, and document-study. The collected data were analyzed using the techniques of qualitative and quantitative descriptive analysis. The result shows that the task implementation and coordination among parties in KUBE program were not effective. To improve the effectiveness of task implementation, the job description and recruitment pattern of supervisors need to be redesigned, while to improve the effectiveness of coordination, communication among parties need to be more intensified.